STRENGTH DEVELOPMENT WITHIN PHYSICAL EDUCATION AND SPORT CLASS IN GYMNASIUM - Trofin Maria Mădălina; Leuciuc Florin (Annals of the “Ştefan cel Mare” University: Physical Education and Sport Section - The Science and Art of Movement, 2018)
This research was fulfilled in order to determine strength development of schoolchildren belonging to secondary school. To achieve this optimization there were chosen two grades, respectively the 6th grade A class and the 6th grade D class of the 9th Elementary School Ion Creanga of Suceava. We started from the following hypothesis: if we use specific methods and tools used for strength development, closely related to the particularities of each age group, we get the desired result, namely the development of the motric skill – strength – and the fulfillment of the goals of Physical Education and Sports subject. Following the used methods and means, there was recorded a progress in final testing.